Genital morphology of female goblin spiders (Arachnida: Araneae: Oonopidae) with functional implications. (19th December 2011) - Burger, Matthias
Abstract Spider genital morphology usually provides the best characters for taxonomy. Furthermore, functional genital morphology helps to understand the evolution of complex genitalia and their role in the context of sexual selection. The genital systems of most haplogyne spider families are poorly investigated with respect to their morphology. The present study investigates the female genitalia of the oonopids Oonops pulcher, Oonopinus kilikus, and Pseudotriaeris sp. by means of light microscopy and SEM. The male palps are briefly described. Females of O. pulcher store spermatozoa in an anterior and a posterior receptaculum (PRe). The genitalia resemble the primitive dysderoid genitalia supporting the hypothesis that the subfamily Oonopinae contains more basal oonopids. In O. kilikus, the anterior receptaculum is reduced to a sclerite. Spermatozoa are stored in a PRe. The receptacula of Pseudotriaeris sp. are reduced to sclerites. Spermatozoa in the uterus internus indicate that fertilization happens there or in the ovary. The anterior sclerite might serve females to lock the uterus during copulation as suggested for other gamasomorphines. The male palp of O. kilikus is simple, whereas the palps of O. pulcher and Pseudotriaeris sp. appear more complex. Complicated structures on the palp of Pseudotriaeris sp. indicate that males exert copulatory courtship.